2004
DOI: 10.1242/dev.01007
|View full text |Cite
|
Sign up to set email alerts
|

Reiterated Wnt signaling during zebrafish neural crest development

Abstract: While Wnt/β-catenin signaling is known to be involved in the development of neural crest cells in zebrafish, it is unclear which Wnts are involved, and when they are required. To address these issues we employed a zebrafish line that was transgenic for an inducible inhibitor of Wnt/β-catenin signaling, and inhibited endogenous Wnt/β-catenin signaling at discrete times in development. Using this approach, we defined a critical period for Wnt signaling in the initial induction of neural crest,which is distinct f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
261
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(272 citation statements)
references
References 90 publications
(88 reference statements)
8
261
1
2
Order By: Relevance
“…In zebrafish, gene knockdown studies demonstrated that wnt8 is required for initial ncc induction (Lewis et al, 2004). We found that activation of the Wnt pathway by incubating embryos in LiCl dramatically increased mdkb expression in neural tissues.…”
Section: Discussion Mdkb Expression Is Regulated By Retinoid But Not mentioning
confidence: 75%
See 3 more Smart Citations
“…In zebrafish, gene knockdown studies demonstrated that wnt8 is required for initial ncc induction (Lewis et al, 2004). We found that activation of the Wnt pathway by incubating embryos in LiCl dramatically increased mdkb expression in neural tissues.…”
Section: Discussion Mdkb Expression Is Regulated By Retinoid But Not mentioning
confidence: 75%
“…It has been shown that reiterative Wnt signaling is crucial for posterior neural development and neural crest induction (Lewis et al, 2004). To test whether mdkb expression is modulated by Wnt activity, embryos were treated with LiCl to inhibit GSK3 activity and ectopically activate the Wnt pathway (Klein and Melton, 1996).…”
Section: Regulation Of Mdkb Expression During Neural Crest Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Canonical Wnt signaling has been associated with development of craniofacial structures and NC derivatives including melanocytes and sensory neural cells (Dorsky et al, 1998;Brault et al, 2001;Hari et al, 2002;Lee et al, 2004;Lewis et al, 2004;Hari et al, 2012). In zebrafish, overexpression of ß-catenin in premigratory NC cells has been shown to promote pigment cell formation at the expense of neurons and glia, while inhibition of Wnt signaling using a truncated form of Tcf3 or a dominant-negative Wnt1 caused an opposite effect promoting neuronal fate at the expense of pigment cells (Dorsky et al, 1998).…”
Section: Role Of Canonical Wnt Signaling In Post-induction Developmenmentioning
confidence: 99%